Sailing mega-solar rafts for huge renewable energy in the low-latitude Pacific Ocean - Takaji Kokusho (Annals of Marine Science - Peertechz Publications, 2023)
An innovative idea of exploiting huge solar energy in the low-latitude Pacific Ocean using wind-sailing mega-solar rafts is reviewed to emphasize its great potential for human renewable energy resources besides currently promoted offshore wind energy. The basic technologies including energy-transportation are already available but necessary to be developed commercially viable. It will also promote the peaceful use of open seas in the Pacific Ocean for a truly sustainable world instead of military confrontations.